2005
DOI: 10.1152/jn.00057.2005
|View full text |Cite
|
Sign up to set email alerts
|

C-type Natriuretic Peptide Inhibits L-type Ca2+Current in Rat Magnocellular Neurosecretory Cells by Activating the NPR-C Receptor

Abstract: (MNCs), of the paraventricular and supraoptic nuclei of the hypothalamus, secrete the hormones vasopressin and oxytocin. As a result, they have an essential role in fundamental physiological responses including regulation of blood volume and fluid homeostasis. C-type natriuretic peptide (CNP) is present at high levels in the hypothalamus. Although CNP is known to decrease hormone secretion from MNCs, no studies have examined the role of the natriuretic peptide C receptor (NPR-C) in these neurons. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…Indeed, the E11 ventricular myocardium has been shown to express high levels of NOS and cGMP proteins compared to the E16 myocardium (Ji et al, 1999) and also to respond to muscarinic and adrenergic stimulation . Activation of NPR-C was shown to significantly inhibit ISO induced Ltype Ca 2þ current (LTCC) via the Gi pathway in adult SA nodal, atrial, and ventricular myocytes (Rose et al, 2003(Rose et al, , 2004(Rose et al, , 2005 (Fig. 7A).…”
Section: Gi and Nos Signaling Form The Basis For Functional Heterogenmentioning
confidence: 98%
“…Indeed, the E11 ventricular myocardium has been shown to express high levels of NOS and cGMP proteins compared to the E16 myocardium (Ji et al, 1999) and also to respond to muscarinic and adrenergic stimulation . Activation of NPR-C was shown to significantly inhibit ISO induced Ltype Ca 2þ current (LTCC) via the Gi pathway in adult SA nodal, atrial, and ventricular myocytes (Rose et al, 2003(Rose et al, , 2004(Rose et al, , 2005 (Fig. 7A).…”
Section: Gi and Nos Signaling Form The Basis For Functional Heterogenmentioning
confidence: 98%
“…NPR-C is initially thought to act as a clearance receptor and lacks the guanylate cyclase domain (12). However, a recent study demonstrated the electrophysiological evidence of a functional role for the NPR-C in the mammalian hypothalamus (13). There are two mechanisms by which CNP is catabolized.…”
Section: Previous Reports Regarding Cnp Production and Metabolismmentioning
confidence: 99%
“…2003, 2004) and central nervous system (Trachte et al . 1995, 2003; Rose et al . 2005) as well as muscular contraction in the gastrointestinal system (Murthy et al .…”
mentioning
confidence: 99%